2021
DOI: 10.1111/jfbc.13866
|View full text |Cite
|
Sign up to set email alerts
|

Taurochenodeoxycholic acid inhibits the proliferation and invasion of gastric cancer and induces its apoptosis

Abstract: Taurochenodeoxycholic acid (TCDCA) is the principal ingredient of Compound Shougong Powder. Despite traditional Chinese medicine (TCM) research demonstrates that Compound Shougong Powder can restrict tumor growth, whether TCDCA exerts a role in suppressing cancer as the major ingredient of Compound Shougong Powder remains unknown. This study aims to clarify the regulatory mechanism of TCDCA on gastric cancer. Gastric cancer cells SGC‐7901 were cultured to investigate the effects of TCDCA on proliferation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…TCDCA inhibited gastric cancer proliferation and invasion and induced apoptosis. Traditional Chinese medicine in experimental studies offered encouraging evidence for the potential application in the blockade of tumor ( Zhang et al, 2022 ). DCA triggered apoptosis in gastric carcinoma cells by activating intrinsic mitochondrial-dependent, p53-mediatedcell death pathway ( Yang et al, 2015 ).…”
Section: The Anticancer Effect Of Natural Basmentioning
confidence: 99%
See 1 more Smart Citation
“…TCDCA inhibited gastric cancer proliferation and invasion and induced apoptosis. Traditional Chinese medicine in experimental studies offered encouraging evidence for the potential application in the blockade of tumor ( Zhang et al, 2022 ). DCA triggered apoptosis in gastric carcinoma cells by activating intrinsic mitochondrial-dependent, p53-mediatedcell death pathway ( Yang et al, 2015 ).…”
Section: The Anticancer Effect Of Natural Basmentioning
confidence: 99%
“…Furthermore, various factors, including gene mutations for the BA synthesis and transport, high-fat diets, medications, and circadian rhythm disturbances, are found to mediate the pathologies of multiple diseases that involve cholestatic liver disease, inflammatory bowel disease, diabetes, obesity, tumors, and related metabolic disorders ( Li and Chiang, 2014 ; Fiorucci et al, 2021 ; Fu et al, 2021 ; Perino et al, 2021 ; Yang et al, 2021 ; Shi et al, 2023 ). In recent years, several researches have demonstrated that BAs have antitumor properties in various cancer cell types, such as tamoxifen-resistant breast cancer ( Luu et al, 2018 ; Kovács et al, 2019 ), oral squamous cell carcinoma ( Talebian et al, 2020 ), cholangiocarcinoma ( Lee et al, 2022 ), gastric cancer ( Zhang et al, 2022 ), colon cancer ( Kim E. K. et al, 2017 ), hepatocellular carcinoma ( Fan et al, 2023 ), prostate cancer ( Lee et al, 2017 ), gallbladder cancer ( Lin et al, 2020 ; Li et al, 2022 ), neuroblastoma ( Trah et al, 2020 ) etc., by inhibiting cancer cell proliferation and migration. In addition, new BA derivatives have been synthesized in several laboratories to investigate their anticancer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Many Chinese monomers inhibit tumor growth [7,8]. Drug components in natural plants cause few adverse reactions owing to their single components and thus allow for a wide range of treatments.…”
Section: Introductionmentioning
confidence: 99%
“…TCDCA is one of the main active ingredients of bear bile powder ( Shi et al, 2017 ). It has been shown that TCDCA is used to treat diseases such as astrocytic neuroinflammation ( Xu et al, 2023a ), pulmonary fibrosis ( Zhou et al, 2013 ), and gastric cancer ( Zhang et al, 2022 ), with inhibitory effects on both acute and chronic inflammation as well as modulating immune responses ( Li et al, 2019 ; Bao et al, 2021 ). Recent studies have reported that TCDCA can reduce intestinal fat transport and treat non-alcoholic fatty liver disease in mice ( Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%